Дополнение к фауне тлей (Homoptera, Aphidoidea) Республики Молдова, характеристика ее состояния и редкие виды - Андреев, А.В.; Верещагин, Б.В. (Вестник зоологии, 1993)
Aphid families are represented over Moldovian territory by following species numbers: Aphididae — 232 Lachnidae-27, Drepanosiphidae — 28, Pemphigidae — 25, Chaitophoridae — 23, Adelgidae —4. Phylloxeridae —4, Anoeciidae — 3, Thelaxidae — 1. Present state of natural vegetation Aphid fauna, species distribution and population are discussed.